Gaps in the structuring of organizations in the graduate employment context in Uganda - Peter Dithan Ntale; Jude Ssempebwa; Badiru Musisi; Genza Gyaviira Musoke; Kimoga Joseph; C. B. Mugimu; Ngoma Muhammed; Joseph Mpeera Ntayi (Journal of Organization Design, 2020)
The complexity of global challenges requires that organizations collaborate with one another. To do this, stakeholders need flexible structures that are designed in a way that allows organizations to collaborate. However, it is not known whether Uganda's organizations are structured in a way that allows them to collaborate with one another, casting doubt as to whether they can manage the complexity of global challenges such as graduate unemployment. Informed by Hage and Aiken (1967), we studied the structures of selected organizations in Uganda and found out that their major components, i.e., centralization and formalization, are designed in a way that may not allow collaboration to occur. We found out that the organizational structures were exclusive in decision-making, had high power distance (HPD), jobs were strictly codified, and organizations enforced stringent rule observation. These gaps make it difficult for people interaction and involvement and deny them of their freedom to relate with one another, making it difficult for a collaboration between different agencies to occur. To enhance organizational collaboration, it is recommended that organizations should be restructured to become more inclusive, interactive, and democratic since organizations structured in this way have shown collaboration success and greater achievement of society needs.
Keywords: 650; Inter-agency collaboration; Graduate employment; Organizational structures; Uganda